Carrier bag storytelling with coastal Kenyan families: sharing food, illustrations, and knowledge for tangible environmental justice impacts - Cohn, Rachel M.; Mbeyu, Ruth; Sarange, Catherine; Mbogholi, Francis; Cheupe, Christopher; Cheupe, Joaquim; Wamukota, Andrew; Kamau, Elizabeth; Treviño, Melva (Frontiers in Communication, 2023)
The small-scale fisheries food system— in which individuals achieve food security independently or in small groups through fishing livelihoods and/or subsistence activities— provides food sovereignty for millions globally. However, this arrangement has inequitable engagement due to strictly enforced gendered roles in many communities, including coastal Kenya. Recently, critics across environmental research disciplines have called for social justice in science through anticolonial, feminist methodologies and interdisciplinary praxis. This resistance may take form through the "carrier bag" ability of fiction: an allusion to Le Guin's visionary analysis of containers as the first cultural device and evidence of the power of a story or personal sovereignty to tell one's story. Drawing from creative, service-driven methodologies emerging from collaboration among international research team members and Indigenous research participants, this project uses the "carrier bag" framework to support local environmental justice and food sovereignty goals through a science storybook resource created and shared with fishing families in Kilifi County, Kenya. We investigate how stories shape interpersonal relations in the context of this collaboration and how health knowledge, environmental science, and representational imagery can be tools for justice by examining the connections between social identity, family values, and social-ecological change in this food system. Having a deeper understanding of the experiences, changing ecosystems, and research feedback of these families allows this work to support fisheries management and nutrition interventions in Kenya and communities elsewhere.